THE EFFECT OF SHAPE PROPERTIES IN GRANULAR SOILS ON SETTLEMENT OF STRIP FOOTING OVERLYING ON SAND - Karimi Ghalehjough, Babak; Akbulut, Suat; Celik, Semet (YILDIZ TECHNICAL UNIV, 2017)
The main objective of this study is to research the effects of roundness, size and relative density of granular soil on the settlement of strip footing placed on soil. For doing this study soil samples has been obtained from calcareous soils with three roundness classes (Angular, Rounded and Well-rounded). Also, the samples have been prepared at 6 different sizes and two relative densities of 50% and 70%. Prepared granular samples with different properties have been subjected to the load by means of a strip footing at this experimental research. The load-Settlement graphs yielded from experimental research showed that the factors of roundness, size and relative density have effects on the ultimate bearing capacity and the value of settlement at failure moment in the granular soils. Research results showed that increasing roundness effected negatively the settlement of footing and caused the soil failure at smaller settlements and ultimate bearing capacity decreased by increasing roundness of particles. Whereas, increasing angularity, grain size and relative density of granular soil samples increased the bearing capacity and decreased the settlement.
Keywords: Roundness of particles; settlement; size of particles; relative density; strip footing; BEARING CAPACITY; Engineering